Nuclear Thermal Hydraulics - Akimoto, Hajime; Anoda, Yoshinari; Takase, Kazuyuki; Yoshida, Hiroyuki; Tamai, Hidesada (An Advanced Course in Nuclear Engineering, 2016)
This volume provides fundamentals of nuclear thermal-hydraulics for reactor design and safety assessment. It also describes the basis for assessing cooling performance of nuclear reactors under accidental conditions. The descriptions in this book are virtually self-contained, beyond the assumption that readers are familiar with the introductory levels of nuclear engineering. This book helps readers understand the processes for nuclear reactor plant design and the most important factors in nuclear thermal-hydraulics.